Новый вид рода кориомерис - Coriomeris Westw. (Hemiptera, Coreidae) из Казахстана - Пучков, В.Г. (Вестник зоологии, 1968)
A new species Coriomeris echinatus Putshkov, sp. n., described according to 4 males and I female from Kazakhstan (reservation Aksu-Dzhabagly) sharply differ from the other representatives of the genus in strongly developed, straight-protruding prickles on the abdomen rim.